2018
DOI: 10.1016/j.amepre.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Level Initiative to Prevent Obesity: Results From Kaiser Permanente’s Healthy Eating Active Living Zones Initiative in California

Abstract: This article is part of a supplement entitled Building Thriving Communities Through Comprehensive Community Health Initiatives, which is sponsored by Kaiser Permanente, Community Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The promotion of health-conducive environments in schools is the focus of new interventions which provide opportunities for engaging in healthy nutrition and physical activity throughout the day [34,[40][41][42][43]. Innovations include attention to breakfast habits, food service in canteens and availability of snacks and drinks in vending machines, bans on drinks except milk and water, healthy snacking breaks, provision of free fresh fruit in the classroom, and engagement with food retailers in the school's surroundings [36,37,[43][44][45][46]. Physical fitness and motor skills tests, awareness building and questionnaires on dietary habits are administered for monitoring uptake of healthy behaviours [47].…”
Section: School-based Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…The promotion of health-conducive environments in schools is the focus of new interventions which provide opportunities for engaging in healthy nutrition and physical activity throughout the day [34,[40][41][42][43]. Innovations include attention to breakfast habits, food service in canteens and availability of snacks and drinks in vending machines, bans on drinks except milk and water, healthy snacking breaks, provision of free fresh fruit in the classroom, and engagement with food retailers in the school's surroundings [36,37,[43][44][45][46]. Physical fitness and motor skills tests, awareness building and questionnaires on dietary habits are administered for monitoring uptake of healthy behaviours [47].…”
Section: School-based Platformsmentioning
confidence: 99%
“…Interventions that impact on health and wellbeing of adolescents (e.g. through increased opportunities for healthy eating, and increased uptake of moderate to vigorous physical activity (MVPA) components) offer second chances to the most disadvantaged [43,50,51,53]. Investments in adolescent health and wellbeing bring benefits not only in their future adult life, but also for the next generation of children as future parents.…”
Section: Out-of-school Time (Ost) Platformsmentioning
confidence: 99%
“…Program coordinators and evaluators who are interested in using dose for planning and implementation can learn more about dose from a National Academy of Medicine white paper 10 and find more detailed methods, tools, and resources in the online dose toolkit 9 and articles included in this special issue. 11,12 Dose methods will hopefully be incorporated more in the planning and implementation phases of CHIs in order to better engage the communities in which these programs are based, and reach the highest number of community members possible. Dose methods in these early planning phases can help ensure community initiatives are maximized effectively with the most buy-in from community members, and the greatest impact on their targeted populations.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Alternatively, some behaviours may be harder to influence than others. For example, Cheadle et al found that consumption of sugary beverages by children decreased after relatively modest community efforts, whereas little change was observed in fruit and vegetable intake after more intense community efforts (24).…”
Section: Discussionmentioning
confidence: 99%